Hypopharyngeal Carcinoma: A Review - Islam, Md. Nazmul; Siddiqui, Mohammad Mamun; Ahmed, Shamsuddin (Journal of Current and Advance Medical Research, 2016)
Hypopharyngeal carcinoma is not a common tumour. Few risk factors increase the risk of this cancer including tobacco smoking, alcohol drinking, chewing of betal nuts. If it is diagnosed in advanced age, its outcome is fatal. So awareness of the risk factors among the persons at risk of this cancer and early diagnosis is recommended. Journal of Current and Advance Medical Research, 2016;3(1):26-30